#### Answer

x = 2(m - 2) / (1 + n)

#### Work Step by Step

2m = x + 4 + nx
2m - 4 = x + nx
2(m - 2) = x(1 + n)
2(m - 2) / (1 + n) = x

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

x = 2(m - 2) / (1 + n)

2m = x + 4 + nx
2m - 4 = x + nx
2(m - 2) = x(1 + n)
2(m - 2) / (1 + n) = x

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.